Comparative efficacy of non-steroidal anti-inflammatory drugs in ankylosing spondylitis: a Bayesian network meta-analysis of clinical trials. Issue 6 (6th August 2015) - Wang, Runsheng; Dasgupta, Abhijit; Ward, Michael M
Abstract : Objective: To compare the efficacy of 20 non-steroidal anti-inflammatory drugs (NSAIDs) in the short-term treatment of ankylosing spondylitis (AS). Methods: We performed a systematic literature review of randomised controlled trials of NSAIDs in patients with active AS. We included trials that reported efficacy at 2–12 weeks. Efficacy outcomes were the change in pain score and change in the duration of morning stiffness. We also examined the number of adverse events. We used Bayesian network meta-analysis to compare effects directly and indirectly between drugs. Results: We included 26 trials (66 treatment arms) of 20 NSAIDs with 3410 participants in the network meta-analysis. Fifty-eight per cent of trials had fewer than 50 participants. All 20 NSAIDs reduced pain more than placebo (standardised mean difference ranging from −0.65 to −2.2), with 15 NSAIDs significantly better than placebo. Etoricoxib was superior to celecoxib, ketoprofen and tenoxicam in pain reduction, but no other interdrug comparisons were significant. There were no significant differences among NSAIDs in decreases in the duration of morning stiffness or the likelihood of adverse events. Adverse events were uncommon in these short-term studies. In 16 trials that used NSAIDs at full doses, etoricoxib was superior to all but two other NSAIDs in pain reduction. Conclusions: Etoricoxib was more effective in reducing pain in AS than some other NSAIDs, but there was otherwise insufficient evidence to conclude that any particular NSAID was more effective in the treatment of AS. Comparisons were limited by small studies.